Evaluation of pyrite and gypsum as a source of sulphur in indian mustard (Brassica juncea)-rice (Oryza sativa) cropping sequence - TRIPATHI, P N; SHARMA, N L (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during winter (1988-89 and 1989-90) and rainy seasons (1989-90 and 1990-91) to evaluate pyrite and gypsum as a source of sulphur in indian mustard [Brassica juncea (L.) Czernj. & Cosson]-rice (Oryza sativa L.) cropping sequence. the sulphur application @ 40 kg/ha gave significantly higher seed (2.10 tonnes/ha) and oil yields (0.80 tonne/ha) of indian mustard. The residual effect of S @ 80kg/ha to indian mustard refiected maximum grain yield (3.22 tonnes/ha) of succeeding rice. The uptake or nutrients (N,P,K,S and Fe) also increased significantly with increase in S level; maximum being (115.30, 17.16, 87.82, 35.48 and 1.16 kg/ha N, P, K, S and Fe respcctively) under 40 kg S/ha by indian mustard and 80 kg S/ha by the succeeding rice crop. Both the sources of sulphur (gypsum and pyrite) were equally effective in increasing the yield and yield components as well as uptake of nutrients by indianÂ  mustard and succeeding rice. However, application of pydie to me preceding indian mustard significantly increased the uptake of Fe by succeeding rice compared with that of gypsum.